TRAVEL GEOGRAPHY OF KERALA: A HISTORICAL PERSPECTIVE - JUSTIN JOSE (Research Guru: Online Journal of Multidisciplinary Subjects, 2019)
Tourism has been projected as the sole savior of Kerala economy, capable of saving it from fiscal crises. Starting from the very first Government formed after State Formation, all Governments of Kerala have given priority to tourism in their plans and policies. Thus, the abundance of natural wealth of the State has been subjected to indiscriminate marketing, in the name of tourism. This paper makes a survey of the geographical resources of Keral a Tourism and analyses the historical transition and transformation of the geography of Kerala due to the development of tourism. The negative and positive impacts of tourism promotion on the geography of Kerala are subjected to criticism.